Sub-acute exposure to nanoplastics via two-chain trophic transfer: From brine shrimp Artemia franciscana to small yellow croaker Larimichthys polyactis. (February 2022) - Kim, Lia; Cui, Rongxue; Kwak, Jin Il; An, Youn-Joo
Abstract: This study investigated the trophic transfer of nanoplastics in marine food chains. We fed nanoplastic-exposed Artemia franciscana (brine shrimp) to Larimichthys polyactis (small yellow croaker) daily for eight days. Subsequently, the overall health condition, histopathological damage to the liver and digestive tract, and swimming ability of the fish were measured. After the sub-acute exposure to nanoplastics via trophic transfer, the fish showed inhibited growth, severe liver damage, as well as a poorer swimming ability compared to the control. The swimming ability was especially affected, in terms of the overall movement as well as thigmotaxis. The results thus clarified that even an indirect exposure to nanoplastics could induce neurotoxic effects and affect the swimming ability of the fish. As fish are well-known human food resources, the possibility of such trophic transfers affecting higher trophic level organisms, such as humans, cannot be ruled out. Highlights: The trophic transfer of nanoplastics (NPs) in a marine food web was investigated. Larimichthys polyactis fed with NP-exposed Artemia franciscana were the subject. NP exposure through trophic transfer led to growth inhibition and liver damage. NP-exposed L. polyactis displayed neurotoxic effects and poor swimming ability. The results clarify the risks of the trophic transfer of NPs in marine food webs.